The Influence of Financial Literacy, Financial Behavior and Financial Technology on Investment Decisions through Locus of Control (Financial Management Literature Review) - Sanjaya, Willy (Dinasti Publisher, 2023)
Literature Review Article on the Effects of Financial Literacy, Financial Behavior and Financial Technology on Investment Decisions through Locus of Control through Locus of Control is a scientific article that aims to build a research hypothesis on the influence of inter-variables to be used in further research , within the scope of Financial Management. The method of writing this Literature Review article is the library research method , which is sourced from online media such as Google Scholar, Mendeley and other academic online media . The results of this article are that: 1) Financial Literacy affects Investment Decisions through Locus of Control; 2) Financial Behavior influences Investment Decisions through Locus of Control; and 3) Financial Technology affects Investment Decisions through Locus of Control. Apart from these 3 exogenous variables that influence the endogenous investment decision variables through Locus of Control there are many other factors including motivational variables, macroeconomics and risk profiles.